Recurrent pyogenic cholangitis - Narendra Pandit; Durga Neupane (Clinical Case Reports, 2023)
Key Clinical Message The incidence of hepatolithiasis is variable. Globalization has additionally altered disease dynamics globally. A multi‐disciplinary team approach is deemed necessary for the timely diagnosis, safe, affordable treatment, and good prognosis.